2007
DOI: 10.1197/j.aem.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Use of Intravenous Procainamide for Patients with Acute Atrial Fibrillation or Flutter

Abstract: This study of acute atrial fibrillation or flutter patients treated in the ED with IV procainamide suggests that this treatment is safe and effective in this setting. Procainamide should be prospectively compared with other ED strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
2
19
0
Order By: Relevance
“…To our knowledge, this is the first systematic review to evaluate the optimal management of AF/AFL in the ED, specifically with regard ED discharge, regardless of the type of acute management that was chosen or rhythm status at time of discharge. It is interesting to note that the articles in the general management group demonstrated a similar rate of short-term adverse events to the articles in the DCCV and chemical cardioversion groups, many of which required patients to convert to NSR in order to be discharged [15,[17][18]20,[25][26][27][28][29][30] . While conversion to NSR seems desirable, particularly in patients with acute onset of AF/AFL, there is no particular reason that persistence of AF/AFL should preclude ED discharge, provided that rate control is adequate and the patient is otherwise stable and not severely symptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first systematic review to evaluate the optimal management of AF/AFL in the ED, specifically with regard ED discharge, regardless of the type of acute management that was chosen or rhythm status at time of discharge. It is interesting to note that the articles in the general management group demonstrated a similar rate of short-term adverse events to the articles in the DCCV and chemical cardioversion groups, many of which required patients to convert to NSR in order to be discharged [15,[17][18]20,[25][26][27][28][29][30] . While conversion to NSR seems desirable, particularly in patients with acute onset of AF/AFL, there is no particular reason that persistence of AF/AFL should preclude ED discharge, provided that rate control is adequate and the patient is otherwise stable and not severely symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…successful conversion rates, respectively [22,23] .The use of IV ibutilide resulted in conversion rates ranging from 64% to 76% [24,25,26,28] . IV procainamide was used by Stiell et al and White et al with a 50% and 67% success rate, respectively [27,30] . Hirschl et al compared a variety of different medications, and found that flecainide (95%) and ibutilide (76%) had the highest rates of conversion to NSR [28] .…”
Section: Electrical Cardioversion-based Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] AF is often first diagnosed in the ED setting and many patients ultimately diagnosed with AF are frequently seen in the ED for AF-related complaints. [12, 13] Our review of 296 patients diagnosed with new AF in the ED over a 3 year-period found nearly half of these patients were seen in the ED prior to the AF diagnosis. The ED presents an opportunity to potentially identify patients at high risk for developing AF and direct these individuals to appropriate interventions that might delay or prevent the onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[12, 13] AF-related complaints include signs (tachycardia, dyspnea) or symptoms (palpitations, chest pain, shortness of breath, weakness, lightheadedness, pre-syncope, or syncope) consistent with symptomatic AF. [12, 13] Pulse measurements and electrocardiograms, both of which are performed regularly in the ED, also diagnose new AF in otherwise asymptomatic individuals. [14, 15] This study's objective was to describe the frequencies of these risk factors and calculate the corresponding risk score in a cohort of ED patients with newly diagnosed AF.…”
Section: Introductionmentioning
confidence: 99%